Introduction - Pohlmann, Markus; Yang, Jonghoe; Lee, Jong-Hee (Citizenship and migration in the era of globalization, 2012)
The twentieth century has been proclaimed as the “Age of Mobility” (Papademetriou 2007) as well as an “Age of Migration” (Castles and Miller 2009). People from all over the world and with vastly diverse social backgrounds are said to be moving and migrating increasingly around the globe. With regard to the developed countries, fears and concern are growing among the general public due to the perception of foreigners pouring into their national homelands. As a consequence the legal concept of citizenship has recently become one of the key issues for political debates revolving around immigration policies. But citizenship is not merely a concept; it is also an emotional issue. The concomitant change in the migrants’ legal status serves as a bureaucratic bottleneck for many other social policy issues, including the citizen’s right to vote - issues that are crucial for the architecture of a modern nation state.
Gesehen am 23.11.2017